Sea level rise outpaced by vertical dune toe translation on prograding coasts - Christa O. van IJzendoorn (Nature Portfolio, 2021)
Abstract Sea level is rising due to climate change and is expected to influence the development and dynamics of coastal dunes. However, the anticipated changes to coastal dunes have not yet been demonstrated using field data. Here, we provide evidence of dune translation that is characterized by a linear increase of the dune toe elevation on the order of 13–15 mm/year during recent decades along the Dutch coast. This rate of increase is a remarkable 7–8 times greater than the measured sea level rise. The observed vertical dune toe translation coincides with seaward movement of the dune toe (i.e., progradation), which shows similarities to prograding coasts in the Holocene both along the Dutch coast and elsewhere. Thus, we suspect that other locations besides the Dutch coast might also show such large ratios between sea level rise and dune toe elevation increase. This phenomenon might significantly influence the expected impact of sea level rise and climate change adaptation measures.